Francisella tularensis-infected human neutrophils are trojan horses for infection of macrophages - Escobar, Sydney M.; McCracken, Jenna; Schwartz, Justin T.; Miller, Ann M.; Allen, Lee-Ann H. (Frontiers in Immunology, 2025)
Francisella tularensis, the causative agent of tularemia, is a Gram-negative bacterium that infects neutrophils (polymorphonuclear leukocytes, PMNs) and macrophages. Previous studies by our group and others demonstrate that F. tularensis inhibits the respiratory burst, escapes the phagosome, replicates in the cytosol, and significantly prolongs human neutrophil lifespan. However, the fate of infected neutrophils and their bacterial cargo are unknown. We now demonstrate that F. tularensis-infected neutrophils (iPMNs) interacted more efficiently with primary human monocyte-derived macrophages (MDMs) than aged, control PMNs despite their viability and paucity of surface phosphatidylserine and identified an important role for serum and C1q in this process. Uptake by this mechanism supported bacterial growth in MDMs, indicating that iPMNs can act as Trojan horses to spread infection. Efferocytosis of apoptotic cells favors repolarization of macrophages from a proinflammatory (M1) phenotype to a pro-resolution (M2) phenotype. In marked contrast, the effects of iPMN were distinct, as these cells elicited an atypical MDM phenotype notable for downregulation of both M1 and M2 surface markers that was accompanied by sustained expression of indoleamine 2,3 dioxygenase and suppressor of cytokine signaling 1 as well as low proinflammatory cytokine secretion. Altogether, our data advance understanding of neutrophil-macrophage interactions and reveal a potential new mechanism for F. tularensis dissemination and immunomodulation within a host.